2004
DOI: 10.1002/asi.20074
|View full text |Cite
|
Sign up to set email alerts
|

Training for Web search: Will it get you in shape?

Abstract: . Two of the experimental treatments were based on the type of training the users received. The first of these treatments was the presence or absence of training on the principles of the use of Boolean operators, henceforth referred to as logic training. The second was the presence or absence of training that focused on the specific characteristics of the assisted search interface, which we will refer to as interface training. The third treatment was the type of interface used by the participants, namely, simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Researchers have repeatedly noted or criticized the simple strategies adopted by many users [16,22]. These criticisms have often identified particular patterns of simplistic searching: limited number of query terms (words); minimal use of search modifiers (phrase search, compulsory terms); poor understanding of Boolean and logical techniques..…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have repeatedly noted or criticized the simple strategies adopted by many users [16,22]. These criticisms have often identified particular patterns of simplistic searching: limited number of query terms (words); minimal use of search modifiers (phrase search, compulsory terms); poor understanding of Boolean and logical techniques..…”
Section: Introductionmentioning
confidence: 99%
“…Several controlled experiments have shown the efficacy of various web search training interventions. Lucas and Topi showed that training users in Boolean logic helped them achieve higher accuracy in their later searches [18]. Harvey et al showed that presenting crowdworkers with query suggestions that were more effective than their own enabled them to later generate higher quality queries [10].…”
Section: Web Search Trainingmentioning
confidence: 99%
“…The findings strongly support the value of providing a novice searcher with both task and search strategy validity feedback. All of the experiments reported in Debowski's (2002) study testify about the need to develop effective search training approaches; even after training, the performance level in these experiments was quite low, as it often is with complex search tasks (see, for example, Sutcliffe, Ennis, and Watkinson (2000) and Lucas and Topi (2004)). Debowski (2002) also points out the importance of integrating training and ongoing support.…”
Section: Review Of Empirical Researchmentioning
confidence: 96%
“…After taking action to execute the query, the searcher must then know how to interpret the results, which is based on system-specific information, such as ordering of results by relevancy; computer usage familiarity, such as using a find feature to search within documents; human intelligence, and other personal characteristics. Figure 2, which first appeared in (Lucas and Topi, 2004), models the learning domain by those human-dependent factors that ultimately affect the success of a search. Search success is defined here, as per Chan, Tan, and Wei (1999) and Te'eni and Feldman (2001), in terms of search performance (correctness/accuracy, time) and searchers' attitudes (confidence and satisfaction).…”
Section: Figure 2: Learning Domain Modelmentioning
confidence: 99%
See 1 more Smart Citation